2016
DOI: 10.1007/s00125-016-4122-1
|View full text |Cite
|
Sign up to set email alerts
|

GAD vaccine reduces insulin loss in recently diagnosed type 1 diabetes: findings from a Bayesian meta-analysis

Abstract: Aims/hypothesis GAD is a major target of the autoimmune response that occurs in type 1 diabetes mellitus. Randomised controlled clinical trials of a GAD + alum vaccine in human participants have so far given conflicting results. Methods In this study, we sought to see whether a clearer answer to the question of whether GAD65 has an effect on C-peptide could be reached by combining individual-level data from the randomised controlled trials using Bayesian meta-analysis to estimate the probability of a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…Randomized controlled trials of GAD alum vaccine have produced inconsistent results. Bayesian meta‐analysis indicated a high probability that GAD with alum administered twice in stage 3 diabetes reduces the loss of C‐peptide by 15% to 20% at 1 year after treatment …”
Section: Intervention At Stage 3 Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized controlled trials of GAD alum vaccine have produced inconsistent results. Bayesian meta‐analysis indicated a high probability that GAD with alum administered twice in stage 3 diabetes reduces the loss of C‐peptide by 15% to 20% at 1 year after treatment …”
Section: Intervention At Stage 3 Type 1 Diabetesmentioning
confidence: 99%
“…Bayesian meta-analysis indicated a high probability that GAD with alum administered twice in stage 3 diabetes reduces the loss of C-peptide by 15% to 20% at 1 year after treatment. 67 Short-term administration of immune modulation therapies that can delay the loss of β-cell function (rate of decline of C-peptide) in patients with recent onset type 1 diabetes includes the anti-CD3 monoclonal antibodies Teplizumab 68 and otelixizumab, Abatacept (CTLA4-Ig), 69,70 Alefacept, 71 and the anti-CD20 monoclonal antibody, rituximab. 72,73 Children and adolescents were participants in these trials and in general had a better c-peptide response to the intervention than adults.…”
Section: Intervention At Stage 3 Type 1 Diabetesmentioning
confidence: 99%
“…Oral insulin has been tried in a prevention setting [17] and post hoc analysis indicated some preventive effect in a subgroup [17]. GAD in alum in T1DM patients showed modest beneficial effects in a recent metanalysis [18]. Insulin B-chain in incomplete Freund's adjuvant (IFA) in a phase 1 clinical trial showed a desirable immune effect by increasing insulin B-chain specific regulatory T cells [19].…”
Section: Resultsmentioning
confidence: 99%
“…The preservation of C-peptide was better the longer the time interval between GAD-alum treatment and the H1N1 vaccination was [93]. Moreover, efficacy was statistically significant in the rather few Swedish patients who were never given the H1N1 vaccination [94]. The results also seemed to be better in patients with high and moderate HLA risk and high GADA concentrations, but less good in patients with low HLA risk and low GADA.…”
Section: Gad As Autoantigenmentioning
confidence: 93%